Comparison of the Diagnostic and Therapeutic Efficacies of Portable Recruited Chest Radiography with Conventional Portable Radiography in Mechanically Ventilated Patients - Sharifpour, Ali (Tanaffos, 2019)
BACKGROUND: In mechanically ventilated patients, portable chest radiography (CXR) can provide important information for selecting the optimal therapeutic approach. This study aimed to determine the diagnostic and therapeutic efficacies of portable recruited chest radiography with maximum inspiratory volume and pause in comparison with conventional portable radiography. MATERIALS AND METHODS: This diagnostic accuracy study was conducted on 75 mechanically ventilated patients admitted to the intensive care unit (ICU) of Imam Khomeini Hospital in Sari, Iran, during 2013–2015. For every patient, in addition to conventional portable CXR, another CXR was performed with mechanical ventilator adjustments (tidal volume up to 10–12 ml/kg to maintain the inspiratory plateau pressure below 35 cmH(2)O and inspiratory time of 2–3 seconds). CXR was performed after 5–10 respiratory cycles, synchronized with the inspiratory pause. The radiographs were acquired using a Shimadzu portable radiography system in the anteroposterior supine position and randomly presented to two radiologists for reporting. RESULTS: The mean age of the patients was 63.5±14 years. Overall, 43 (57.3%) patients were male, and 32 (42.7%) were female. Therapeutic interventions were performed for only 8% of cases with conventional CXR versus 21.3% of cases with recruited CXR; the difference was found to be statistically significant (P<0.05). The diagnostic efficacy of portable recruited CXR versus conventional portable CXR was 45% versus 18.6%. Also, the therapeutic efficacy of portable recruited CXR versus conventional portable CXR was 21.3% versus 8%. CONCLUSION: Portable recruited CXR seems to be a valuable diagnostic approach for clinical decision-making, with higher diagnostic and therapeutic efficacies in mechanically ventilated patients.